2007
DOI: 10.1038/sj.npp.1301291
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine Prevents Anhedonia Induced by Acute or Chronic Stress

Abstract: The role of atypical antipsychotics as add-on treatments and as primary mood stabilizers in different phases of bipolar disorder is an important current research area. Although in bipolar patients the main therapeutic indication of quetiapine (QTP) is the management of acute mania, several observations suggest that this agent may exert antidepressant as well as antimanic effects. However, in our knowledge, there are no preclinical studies supporting this hypothesis. Thus, the main goal of the present work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…Previous studies report that the second-generation antipsychotics olanzapine and quetiapine reverse CMS-induced 'anhedonia' (Orsetti et al, 2006(Orsetti et al, , 2007. In support of these results, we demonstrated that olanzapine reversed CMSinduced decreases in sucrose consumption without affecting controls.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies report that the second-generation antipsychotics olanzapine and quetiapine reverse CMS-induced 'anhedonia' (Orsetti et al, 2006(Orsetti et al, , 2007. In support of these results, we demonstrated that olanzapine reversed CMSinduced decreases in sucrose consumption without affecting controls.…”
Section: Discussionsupporting
confidence: 87%
“…The involvement of a metabolite in quetiapine's antidepressant action in humans was also suggested by published animal studies showing antidepressant-like activity after chronic, but not acute, administration (Orsetti et al, 2007;Yan et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, the atypical antipsychotics olanzapine and quetiapine, but not the classical agent haloperidol, reverse stress-induced anhedonia (Orsetti et al, 2007), suggesting the possible relevance of this procedure for assessing novel antipsychotics.…”
Section: Anhedoniamentioning
confidence: 99%